2020
DOI: 10.1097/meg.0000000000001740
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Helicobacter pylori eradication in preventing metachronous gastric cancer and preneoplastic lesions. A systematic review and meta-analysis

Abstract: Background: Helicobacter pylori is a significant risk factor for gastric cancer. Recent trials show eradication decreases the incidence of gastric cancer in patients with early-stage gastric cancer. However, data on gastric cancer prevention are inconsistent for patients with precancerous lesions such as atrophic gastritis and intestinal metaplasia. Aim: The aim of the study is to assess the efficacy of H. pylori eradic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 47 publications
0
14
0
2
Order By: Relevance
“…Non-coding RNA (ncRNA) constitute the majority of the human transcriptome, including a class of small ncRNAs (including miRNAs and piRNAs), lncRNAs and circular RNAs (25)(26)(27). Increasing studies have reported that miRNAs play critical roles in tumorigenesis and metastasis and could serve as diagnostic and prognostic biomarkers for cancer-related patients (28).…”
Section: Discussionmentioning
confidence: 99%
“…Non-coding RNA (ncRNA) constitute the majority of the human transcriptome, including a class of small ncRNAs (including miRNAs and piRNAs), lncRNAs and circular RNAs (25)(26)(27). Increasing studies have reported that miRNAs play critical roles in tumorigenesis and metastasis and could serve as diagnostic and prognostic biomarkers for cancer-related patients (28).…”
Section: Discussionmentioning
confidence: 99%
“…It may be due to the fact that among the selected cases reported above those with negative HP infection or that had turned negative after treatment were not strictly screened, given that the surface erosive ulcer was reported to be closely correlated with HP infection. [18][19][20][21] Therefore, it is still doubtful whether the erosive ulcer at the lesion site in the above report above can be used as an independent risk factor if not excluding HP factors. In this study, all patients selected showed positive results in HP infection after the first examination and underwent quadruple bactericidal therapy.…”
Section: Discussionmentioning
confidence: 99%
“…dyspepsia (41). Other studies analysed the role of H. pylori eradication on the incidence of metachronous gastric cancer and preneoplastic lesions such as atrophic gastritis and intestinal metaplasia after treatment of early gastric cancer (41,43,44). H. pylori eradication appeared to be associated with reduced gastric cancer incidence in these patients as well as with an improvement in atrophic gastritis and intestinal metaplasia.…”
Section: H Pylori Infection Can Be Diagnosed Using Invasive (Endoscop...mentioning
confidence: 99%